Analysis of Electrical Properties of Copper Bars Obtained from Electrical Waste - PHAKVISETH, Pem; PHIMMAVONG, Kongsy; NANTHAVONG, Bounphong; SENGPASEUTH, Bouthamaly; KENENAVONG, Southida (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The purpose of this study is to study the copper refining process, wasted copper scrap, and the physical and electrical properties of melted metallic copper. At the same time, it is being researched as a means of promoting and developing the copper sector for individuals who choose to pursue additional studies. 900°C, 1030°C, 1040°C, 1050°C, and 1080°C with a burning time of 30 minutes to 1 hour, take the sample that melts into a liquid metal to form a copper ingot, then take the copper ingot sample to analyze the density, the surface of the metal ingot, the chemical composition of the copper sample, and the electrical conductivity coefficient. The research found that wire scraps brought in at this time are melted at a temperature of 1040ºC but are still not fully melted down. At a temperature of 1050ºC, it can be melted into liquid metal and made into a copper metal bar, it has a density equal to 7.91 g/cm3, and at a temperature of 1080ºC, it has a density of 8.63 g/cm3. The results of photographing copper metal under a microscope indicate that the color of the copper metal is brown, the rough surface is made up of holes and small scratches, and the microstructure of the copper metal is visible. The average electrical conductivity coefficients of copper bars burned at 1040°C, 1050°C, and 1080°C were 1150.62 ´ 103 (S/m), 557.15 ´ 103 (S/m), and 395.11 ´ 103 (S/m), respectively. Therefore, to manufacture copper metal scraps, discarded or degraded electrical wires can be burned at temperatures ranging from 1050ºC to 1080ºC, following a mold-making process.